Chromogranin A in the early steps of the neurosecretory pathway. Issue 4 (30th December 2019) - Laguerre, Fanny; Anouar, Youssef; Montero‐Hadjadje, Maité
Abstract: Chromogranin A (CgA) is a soluble glycoprotein stored with hormones and neuropeptides in secretory granules (SG) of most (neuro)endocrine cells and neurons. Since its discovery in 1967, many studies have reported its structural characteristics, biological roles, and mechanisms of action. Indeed, CgA is both a precursor of various biologically active peptides and a granulogenic protein regulating the storage and secretion of hormones and neuropeptides. This review emphasizes the findings and theoretical concepts around the CgA‐linked molecular machinery controlling hormone/neuropeptide aggregation and the interaction of CgA‐hormone/neuropeptide aggregates with the trans ‐Golgi membrane to allow hormone/neuropeptide targeting and SG biogenesis. We will also discuss the intriguing alteration of CgA expression and secretion in various neurological disorders, which could provide insights to elucidate the molecular mechanisms underlying these pathophysiological conditions.